Intra-prediction mode decision based on video temporal and spatial correlation - DAI Sheng-kui; YU Li; ZHU Guang-xi; LIU Wen-yu (Tongxin xuebao)
An intra-prediction mode-decision method was proposed. Based on the inherent spatial correlation within a single frame and temporal correlation between successive frames, part of intra-prediction modes were chosen to determine the best prediction mode for image block, which resulted in directly reducing the computational complexity and maintaining high coding efficiency. In addition, a complexity-scalable technique was presented to control the complexity of intra prediction, by which the video coder was matched to the limited computational resource of communication equipments. The proposed methods are verified in AVS-M software platform.